On the effect of calcium lignosulfonate on the rheology and setting time of cement paste. (October 2017) - Colombo, A.; Geiker, M.R.; Justnes, H.; Lauten, R.A.; De Weerdt, K.
Abstract: The effect of softwood calcium lignosulfonate, LSs, on the rheology and setting time of cement paste has been investigated. Two Portland cements with different surface area and C3 A content were used. The lignosulfonate was added either immediately with the mixing water or delayed after 10 min of hydration. The cement pastes were characterized in terms of specific surface, rheology and heat of hydration. Extracted pore solutions were analysed for free lignosulfonate concentration and for changes in elemental composition. Immediate addition of LSs increased the specific surface, but not delayed addition. Correlations were found between rheology and surface coverage by LSs, as determined by adsorption isotherms, and between the setting time and the amount of free LSs in the pore solution. An increased setting retardation upon delayed addition related to an increased concentration of Al in the pore solution.